Genealogies of Environmental Media: Feminist Art and the Choreographic Body in Social Works - Sarah Lerner (Media + Environment)
"Genealogies of Environmental Media" analyzes a feminist genealogy of art and media practice that reconstitutes the relationship between bodies and environments through what Shannon Jackson calls "social works"---artworks that are engaged at the nexus of aesthetics and politics. I attend to social works that focus on the environment, and in so doing, reveal a feminist strategy of performance that I refer to as the *choreographic body*. The choreographic body enacts the labor of performance and alters the embodied experience of spectators and participants. As media bodies, choreographic bodies are semiotic and historically contingent, advancing environmental work in ways that foreground how the performing body exposes environmental infrastructures that are occluded from view. In the social works I analyze, the choreographic body occupies a site of reflexive mediation that bears on the environment, lacing feminist art with media histories. \ I trace the changing status of the choreographic body alongside environmental social work beginning with filmmaker Maya Deren's *choreocinema* and dancer Anna Halprin's community dance to illustrate how the choreographic body developed as a feminist strategy---shifting from explorations of the body in front of the camera in the outdoors, to dance's shifting location from inside the studio to outside on Halprin's dance deck and in the wider California community. This foundation then recasts performance artist Mierle Laderman Ukeles through the lens of dance as an overlooked, but central, part of her environmental practice. I read *Touch Sanitation* and *Marrying the Barges: A Barge Ballet/Touch Sanitation Show* in light of how she utilizes the choreographic body as an overlooked feminist strategy. This positions the bodies of participants in a larger choreography of performance. Finally, I analyze *Invisible-5*, a travelogue/audio tour of Interstate 5 in California that brings awareness to environmental injustice, as a way to think through the shifting role of the choreographic body in more recent work and ask where it might lead us as scholars and activists.